Analisis Kinerja Keuangan Pada Perusahaan Manufaktur Sub Sektor Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia - Dharmawaty Djaharuddin (Insan Cita Bongaya Research Journal, 2023)
This study aims to determine the analysis of liquidity (CR) and Solvency (DER) variables on financial performance (ROA) in food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange for the 2019-2021 period. This data collection uses secondary data in the form of financial statements of consumer goods industry companies. This type of research uses quantitative research methodology. The population in this study is the consumer goods industry and the sample of the 2019-2021 research period. The population is 15 food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange for the 2019-2020 period. With 11 samples selected using purposive sampling techniques. The quantitative results of the classical assumption test are in the form of Normality, Multicolonicity, and Heteroscedasticity tests. This analysis method uses Multiple Linear regression techniques. With coefficient test, determination and t test. The results showed that the Liquidity variable (CR) partially had a significant effect on Financial Performance in the Profitability (ROA) proxy and the Solvency (DER) variable had no significant effect on Financial Performance in the Profitability (ROA) proxy.